Jump Start Vue.js - Jacques, Nilson (SitePoint Pty. Ltd., 2019)
Get up to speed with Vue.js in a weekend! Since its release in 2014, Vue.js has seen a meteoric rise to popularity and is now considered one of the primary front-end frameworks, and not without good reason. Its component-based architecture was designed to be flexible and easy to adopt, making it just as easy to integrate into projects and use alongside non-Vue code as it is to build complex client-side applications. This short book is ideal for front-end developers who need a rapid introduction to Vue.js. It covers: Basic concepts: how Vue works, tempmlates, and reactive data Components: custom components, events and slots State management: Vuex, mutations, actions Routes: creating routes, links and route guards Nuxt.js And much more!